Generation z's perceptions of health information about the Covid-19 - Nursanti, Siti; Dharta, Firdaus Yuni; Chaerudin, Chaerudin; Syam, Syisea Putri; Purnama, Rifki Nugraha (Jurnal Studi Komunikasi, 2022)
The COVID-19 pandemic has spread widely worldwide, and Indonesia is no exception. It has led the government to enforce an imperative policy, advising most activities to be done at home by everyone, including Generation Z, that has lived and grown up among the advances in communication and information technology. This study examines Generation Z's perceptions of health information regarding the COVID- 19 pandemic. This study was conducted utilising a quantitative research technique utilising a survey methodology. In this study, it was found that Generation Z firstly learned about the emergence of the COVID-19 virus on the internet, especially on social media. No negative perception was found from Generation Z related to any information shared on the internet, including their social media. Additionally, the study found that getting health information through social media was their choice, closely related to their daily activities.